ADDITIVE TECHNOLOGIES AND PROFILING OF GENERAL PURPOSE DRONES: THE FUTURE OF AVIATION - A.I. Vlasov; A.V. Garaev; V.O. Zakharova; K.V. Selivanov; D.D. Chernyshov (Надежность и качество сложных систем, 2024)
Background. The paper analyzes modern additive technologies and their application for the production of unmanned aerial vehicles. The methods and means of UAV profiling based on additive technologies have been systematized and generalized. The possibilities of additive technologies and their advantages in comparison with traditional technologies for the production of parts of various machines are systematized. Materials and methods. The main attention is paid to the methods of creating components of UAVs based on additive technologies. The model range of drone parts, the production of which is possible by using additive technologies is formed, the advantages and disadvantages of using these parts in the production of unmanned machines are analyzed. Results and conclusions. An algorithm for UAV profiling methodology based on additive technologies has been developed and recommendations for engineers and technologists on optimization and implementation of additive technologies for creating parts and components for unmanned aerial vehicles have been given.